Effect of Oxygen-Reducing Atmospheres on the Safety of Packaged Shelled Brazil Nuts during Storage - Vildes Maria Scussel; Barbara Nantua Giordano; Vanessa Simao; Daniel Manfio; Simone Galvao; Manuel Nazaré Ferreira Rodrigues (International Journal of Analytical Chemistry)
This work reports the application of oxygen-(O2-) reducing atmosphere methods on stored shelled Brazil nut (Bertholletia excelsa H.B.K.) packs aiming to evaluate the degree of aflatoxin degradation, nuts lipid oxidative stability, fungi control, and hygienic conditions improvement. The methods applied were (a) ozone: O3, (b) carbon dioxide: CO2, and (c) O2 absorber pads with and without vacuum. From all modified atmospheres evaluated, the best performance was obtained with O3, either with or without vacuum. It was the only nut treatment that was able to degrade aflatoxins. None of the spiked (AFLs: 15 μg·kg−1) nut samples O3- treated had aflatoxins detected up to the LC-MS/MS method LOQ (0.36 μg·kg−1 for total AFLs), thus producing safer nuts. Also it kept the fatty acid oxidation indicator—malondialdehyde stable and improved the sensory attributes for consumer acceptance. In addition, the destruction of fungi and yeast was observed since the O3 application (from 1.8×104 cfu/g to NG = no growth). All other treatments stabilized and/or inhibited microorganisms' growth only. By adding CO2 gas also played an important role in the nut quality. Regarding cost, gaseous O3 showed to be of low cost for application in the nut packs.